The comparison of the Functional Movement Screen test results of volleyball national team players in different countries - Aka, H.; Yilmaz, G.; Akarcesme, C.; Altundag, E. (Journal of Education and Learning, 2019)
This study was conducted to compare the functional movement patterns of female volleyball players from different countries. 34 the women`s volleyball national team athletes from three different countries participated in the study; Turkey (n=9), Azerbaijan (n=16) and Kyrgyzstan (n=9). Functional movement screen of the athletes were determined by the Functional Movement Screen (FMS) test kit. The Kruskal-Wallis H Test was used for multiple comparisons from nonparametric tests in determining the difference between functional movement patterns of national teams. At the end of the study, it was determined that the FMS total scores of the teams were higher than 14 points which were considered as critical limits and there was no statistically significant difference between the FMS total scores of the teams (p<0.05). However, there were significant differences between the teams in the hurdle step, shoulder clearing test and shoulder mobility tests which formed the FMS test battery. As a conclusion, the fact that volleyball players in each country have more than 14 points of FMS total score, which is the critical limit, shows that volleyball players have low risk of injury. This may be related to the elite level of volleyball players and the implementation of correct training models.